Design of 2n factorial experiments for their analysis with Infostat and Infogen - Pérez López, Delfina de Jesús; Franco Martínez, J. Ramón Pascual; Gutiérrez Rodríguez, Francisco; Hernández Ávila, Jesús; Balbuena Melgarejo, Artemio; González Huerta, Andrés (Revista Mexicana de Ciencias Agrícolas, 2021)
The design and analysis of data from factorial experiments using statistical packages saves time, simplifies calculations, and allows discussion of the individual or joint contribution of several factors. This study indicates the procedures for analyzing data with the InfoStat and InfoGen statistical packages in 2n factorial experiments, with n= 2, 3, 4, 5, 6, 7 and 8 factors of productivity. In addition, the design of its treatment structure, possible interactions, statistical models for a randomize complete block design and some formulas for calculating sums of squares for n= 8 are shown. The relationships between the linear models are established and also the procedures that must be applied in both statistical packages to obtain an analysis of variance and the comparison of treatment means if the general statistical model is used, the instructions to estimate the effects for each of the eight main factors and for their possible interactions with the Tukey test (p= 0.01) are also indicated. The design of this type of experiments was made to be analyzed with academic test versions, which are free for six months in both statistical packages. The user could purchase a license for one year to install it on two personal computers paying, for each software, only USD50.00. Both statistical packages are very friendly and can be used to analyze any experimental design if the appropriate statistical model is indicated.